2013
DOI: 10.1161/circep.113.000266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obstructive Sleep Apnea and its Treatment on Signal-Averaged P-Wave Duration in Men

Abstract: The online-only Data Supplement is available at http://circep.ahajournals.org/lookup/suppl/doi:10.1161/CIRCEP.113.000266/-/DC1. Correspondence to Ken-ichi Maeno, MD, Sleep Center, Toranomon Hospital, 2-2-2 Toranomon, Minato-ku, Tokyo 105-8470, Japan, E-mail maeken@zk9.so-net.ne.jp Background-Prolonged P-wave duration, indicating atrial conduction delay, is a potent precursor of atrial fibrillation.Obstructive sleep apnea (OSA) is a risk factor for atrial fibrillation development. We investigated the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Atrial and atrioventricular (AV) conducting system ERPs were defined as the longest S1-S2 coupling interval failing to generate a propagated beat. To assess atrial tachyarrhythmia inducibility, 25-Hz burst pacing (pulse width 2 ms, 4 Â threshold current) was applied for 3 s, with 6 3-s burst cycles separated by 1-s intervals. AF was defined as a rapid (>800 beats/min) irregular atrial rhythm, and AF inducibility was defined as AF lasting for at least 1 s immediately after the 6-burst cycle protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial and atrioventricular (AV) conducting system ERPs were defined as the longest S1-S2 coupling interval failing to generate a propagated beat. To assess atrial tachyarrhythmia inducibility, 25-Hz burst pacing (pulse width 2 ms, 4 Â threshold current) was applied for 3 s, with 6 3-s burst cycles separated by 1-s intervals. AF was defined as a rapid (>800 beats/min) irregular atrial rhythm, and AF inducibility was defined as AF lasting for at least 1 s immediately after the 6-burst cycle protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with OSA exhibit prolonged atrial conduction times, longer P waves, slowed atrial conduction velocities, lower atrial electrogram voltages, and more complex electrograms (11,24). Signal-averaged P-wave duration is increased by OSA and significantly decreases Repetitive OSA Causes AF-Promoting Remodeling with continuous positive airway pressure treatment (25). OSA is also associated with LV hypertrophy and dilation, as well as an increased risk of systolic dysfunction (26).…”
Section: Relationship To Clinical Observations Andmentioning
confidence: 99%
“…117,118 Signal-averaged P-wave duration is increased by OSA, and decreases significantly with continuous positive airway pressure treatment. 120 In a rat model, repeated obstructive apnoea over a 4-week period increases AF vulnerability and slows atrial conduction by altering connexin-43 expression and inducing atrial fibrosis. 121 …”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%
“…Arousal increases vagal tone in the transmission structures of the heart, which increases the PR interval. Maeno et al demonstrated that apnea/hypopnea prolongs the P wave independently (10) . Somer et al showed that barorefl ex distortion and the increase of chemo-refl ex response are due to sympathetic and parasympathetic changes in patients (11) .…”
Section: Discussionmentioning
confidence: 99%